Biphalin, a Dimeric Enkephalin, Alleviates LPS-Induced Activation in Rat Primary Microglial Cultures in Opioid Receptor-Dependent and Receptor-Independent Manners - Katarzyna Popiolek-Barczyk; Anna Piotrowska; Wioletta Makuch; Joanna Mika (Neural Plasticity)
Neuropathic pain is relatively less responsive to opioids than other types of pain, which is possibly due to a disrupted opioid system partially caused by the profound microglial cell activation that underlines neuroinflammation. We demonstrated that intrathecally injected biphalin, a dimeric enkephalin analog, diminished symptoms of neuropathy in a preclinical model of neuropathic pain in rats (CCI, chronic constriction injury of the sciatic nerve) at day 12 postinjury. Using primary microglial cell cultures, we revealed that biphalin did not influence cell viability but diminished NO production and expression of Iba1 in LPS-stimulated cells. Biphalin also diminished MOP receptor level, as well as pronociceptive mediators (iNOS, IL-1β, and IL-18) in an opioid receptor-dependent manner, and it was correlated with diminished p-NF-κB, p-IκB, p-p38MAPK, and TRIF levels. Biphalin reduced IL-6, IL-10, TNFα, p-STAT3, and p-ERK1/2 and upregulated SOCS3, TLR4, and MyD88; however, this effect was not reversed by naloxone pretreatment. Our study provides evidence that biphalin diminishes neuropathy symptoms, which might be partially related to reduced pronociceptive mediators released by activated microglia. Biphalin may be a putative drug for future pain therapy, especially for the treatment of neuropathic pain, when the lower analgesic effects of morphine are correlated with profound microglial cell activation.